POSITRON ANNIHILATION IN DEFECTS NATURE OF HYDROGEN IN REFRACTORY METAL ALLOYS - Aliev, B.A.; Mukashev, K.M.; Tronin, B.A. (Recent Contributions to Physics, 2018)
The possibility of applying the method of positron spectroscopy to study structural defects is discused. The defects created by deformation and hydrogenation. Positrons are sensitive to defects introduced by hydrogen atoms. The defects affect the electronic structure of the material. Change of annihilation parameters indicate the evolution of structural defects in metals and alloys. Such information is important for fundamental studies of the process of generation and dynamics of the interaction of point defects.